MORPHOLOGICAL FEATURES OF THE UZBEK LANGUAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses various dialects found among the people, their uniqueness, their place and significance in the Uzbek language. It discusses the relationship of the Uzbek literary language to dialects, their place in the language system, and the state of their use among the people.